Hiperatividade/défice de atenção : um olhar psicodinâmico - Sargento, José (2016)
Revista de Psicologia da Criança e do Adolescente. - ISSN 1647-4120. - V. 7, n. 1-2 (Janeiro-Dezembro 2016). - p. 31-36.